As disputas territoriais na formação do assentamento Canudos, em Goiás - Anacleto, Álvaro [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
In Brazil the development of capitalism in agriculture promoted the concentration of land and established a model of development and field production with priority given to large farms, at the expense of peasant units, that is the main problem that structures the agrarian question in the country. In this work we have as main objective to analyze the territorial dispute between capitalist agriculture (today represented mainly by agribusiness) and the peasantry, with the case study of Canudos settlement, in the state of Goiás, and having reference to agrarian formation of the state of Goiás. The struggle for land held by Sem Terras is highlighted as essential to explain the conflict between the two territories: capital and peasantry. We believe that these models of development are antagonistic and therefore establish relations of coping for territorial control. Theoretically, we rely on paradigmatic debate, that seeks to explain the Brazilian agrarian question, which considers two main paradigms: the Paradigm of Agrarian Capitalism (PCA) and the Paradigm of Agrarian Question (PQA). Theoretically, we are positioned ourselves alongside the assumptions of PAQ, that at general analyzes the agrarian question from the problems generated by the development of capitalism on the countryside. We also analyze the struggle for the land in Goiás, with focus on the struggles waged by the MST. The case study of Canudos settlement presents a historical trajectory of families and of the process of consolidation of the settlement, subsequently, the struggle to remain on the land and resist attempts to repossession of capital in the settlement via partnership proposals. Thus, we identified which directly impacts the lives of families have access to public policies that promote production and marketing, as the Food Acquisition Program (PAA)

No Brasil o desenvolvimento do capitalismo na agricultura promoveu a concentração da terra e estabeleceu o modelo de desenvolvimento e produção do campo com prioridade para as grandes propriedades em detrimento das unidades camponesas, sendo este o principal problema que estrutura a questão agrária no país. Nesta dissertação temos como objetivo principal analisar a disputa territorial entre a agricultura capitalista (na atualidade representada principalmente pelo agronegócio) e a camponesa, tendo como caso de análise o assentamento Canudos, no estado de Goiás. O caso do assentamento Canudos é analisado tendo como quadro de referência a formação agrária do estado de Goiás e a luta pela terra realizadas pelos Sem Terras é destacada como elemento primordial para explicar a conflitualidade entre os dois territórios: o capital e o campesinato. Consideramos que esses modelos de desenvolvimento são antagônicos e, por isso, estabelecem relações de enfrentamento pelo controle territorial. Teoricamente nos baseamos no debate paradigmático que busca explicar a questão agraria brasileira, o qual considera dois principais paradigmas: o Paradigma do Capitalismo Agrário (PCA) e o Paradigma da Questão Agrária (PQA), sendo que nos posicionamos teoricamente ao lado das assumpções do PQA que, de modo geral, analisa a questão agrária a partir dos problemas gerados pelo desenvolvimento do capitalismo. Analisamos também a luta pela terra em Goiás, com enfoque às lutas realizadas pelo MST. O estudo de caso do assentamento Canudos apresenta um resgate histórico da trajetória das famílias e do processo de consolidação do assentamento e, posteriormente, a luta pela permanência na terra e resistência às tentativas de reterritorialização do capital no assentamento via propostas de parceria...
Keywords: Geografia; Camponeses - Goias (Estado); Agroindústria - Goias (Estado); Assentamentos humanos - Goias (Estado); Reforma agraria - Goias (Estado); Territorialidade humana; Geography